Certainty Cognitive Map (CCM) for Accessing Cognitive Map Causality Using Certainty Factors for Cardiac Failure - Sumiati, .; Hoga, Saragih; T.K.A, Rahman; Agung, Triayudi (2021)
This study aims to resolve existing problems, which is to resolve weaknesses that have both the certainty factor approach and the cognitive map approach in diagnosing cardiac failure, so that the Certainty Cognitive Map (CCM) approach is used to diagnose cardiac abnormalities, which is an approach of certainty factor modification and Cognitive Map (CM) modification. The results of the study show that with the Certainty Cognitive Map (CCM) approach, it is able to form an intact cognitive map where a causal relationship is seen between the evidence with other evidence, and certainty cognitive map is able to have one evidence value with other evidence, the causality value of abnormal cognitive maps include: causality value of E1 to E2 of −0.6, E2 of E6 of −0.6, E6 of E12 of −0.64, E1 of E13 of −0.64, E14 to E15 amounted to −0.85, E1 to E6 amounted to −0.6, E6 against E7 of −0.64, E7 of E8 of −0.85, E7 of E9 of −0.94, E9 of E10 of 0.25, E10 of E11 of −0.84, E8 of E3 of −0.94, E3 against E4 of −0.97, E4 of E5 of −0.93, E2 of Abnormal at −0.99, E12 of Abnormal at −0.24, E15 of Abnormal at 0.71, E16 of Abnormal at −0.36, E11 against Abnormal at −0.69 and E5 against Abnormal at 0.93, while the normal cognitive causality map values are as follows: E1 against E2 of −0.8, E2 to E3 of 0.84, E3 of E4 of 0.6, E4 of E5 of 0.24, E3 of E4 of 0.6, E5 of E7 of 0.02, E7 against E8 of −0.95, E3 of E9 of 0.89, E9 of E10 of −0.84, E10 of E11 of −0.44, E11 of E12 of −0.13, E2 of E3 of 0.84, E3 to E4 of 0.6, E4 to E10 of 0.47, E10 to E13 of −0.66, E6 to Normal of −0.22, E8 to Normal of 0.77, E12 to Normal of −0.72 and E13 against Normal of 0.84.